The Role of the Government in Responding to Street Vendors' Resistance to the Ban on Selling in the Pasar Raya Area of Padang City - Fala, Muthia; Akmal , Artha Dini (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the role of the Padang City Government in responding to the resistance of street vendors (PKL) against the policy prohibiting trading in the Pasar Raya area of Padang City. The policy was implemented to create an orderly, clean, and aesthetic urban space by relocating the vendors to the newly built Phase VII Market Building. However, the relocation policy triggered resistance from the vendors who viewed it as neglecting their economic and social conditions. This research employed a descriptive qualitative approach, using interviews, observations, and documentation as data collection techniques. The findings reveal that the government’s roles as a stabilizer, innovator, modernizer, pioneer, and implementer have not been optimally carried out. The main obstacles include low vendor participation, insufficient socialization, weak inter-agency coordination, and limited facilities in the new location. The study concludes that the government needs to adopt participatory and dialogical approaches to manage social resistance effectively. Such approaches are essential for ensuring that public policies are both equitable and sustainable in addressing the economic interests of marginalized urban communities.